The Fisher Effect and the Term Structure of Interest Rates: Tests of Cointegration - Wallace, Myles S.; Warner, John T. (The Review of Economics and Statistics, 1993)
The literature on the Fisher effect has ignored the potential relationship between inflation and long-term interest rates. Using an expectations model of the term structure of interest rates, the authors establish the conditions under which innovations in short-term inflation will be transmitted to long-term as well as short-term interest rates. Cointegration tests find support for both the Fisher effect and the expectations theory of the term structure. Copyright 1993 by MIT Press.